Ефективність використання ші для розробки відеоігр - Платов, М. В. (ХНУРЕ, 2025)
The rapid development of artificial intelligence (AI) has significantly impacted the video game industry, enhancing both individual and team-based development processes. AI automates routine tasks, accelerates content generation, improves NPC behavior, and optimizes game mechanics. However, its integration raises ethical concerns, such as the originality of AI-generated content and the potential replacement of human specialists. While some studios, like Activision, reduce staff and rely more on AI, experts argue that AI should be a tool to assist developers rather than a means to maximize profits by cutting jobs.
Keywords: розробка відеоігр; video game industry